Avaliações clínicas, hematológicas e radiográficas de pacientes portadores de periodontite crônica sob uso sistêmico da sinvastatina como adjuvante ao tratamento periodontal não cirúrgico – ensaio clínico randomizado - Teles, Patrícia de Barros (2018)
Chronic periodontitis (CP) is a complex and multifactorial disease characterized by inflammation in the supporting tissues of the teeth. Simvastatin (SMV) is used to dyslipidemic treatment, with antinflammatory, immunomodulatory and antireabsortive pleiotropic effects. The aim of this study was to investigate the effect of systemic use of simvastatin as adjuvant therapy to scaling and root planning (SRP) on clinical and radiographic parameters. Patients were randomized into two groups to receive systemic SMV (20 mg/day, n=10 patients, 165 sites) or placebo (n=11 patients, 108 sites) daily for 6 months. Blood samples were collected for the measurement of blood count cells, coagulogram, alkaline phosphatase, lipid values, hepatic enzymes and calcium levels prior treatment (T0) and were repeated 6 months (T6) following SRP. Clinical measurements of periodontal parameters included: probing depth (PD), clinical attachment level (CAL), plaque index (PI), gingival index (GI), percentage of sites with bleeding on probing (BOP%), on T0, T3 and T6. Radiographic parameters included: linear distances measurements (LM) and analysis of the gray levels (GL) after digital radiographic subtraction (DRS) on T0, T6 and T12. Data showed that leucocytes count were higher in the control group on T6. None significative difference was seen in others hematologic parameters. Clinical and radiographic parameters were significatively improved in both groups, but SMV group showed better response when PD reduced to ≤3 mm (94.4%) and CAL ≤3 mm (59.3%) compared to CONTROL group (80% and 46.7%, respectively; p˂0,01). Deeper sites (PD≥6 mm) showed better response to treatment on SMV group where 90.2% reduced to ≤3 mm, compared to CONTROL group (62%; p˂0.01). Vertical angles (≤22°) showed better gain of bone (2.79 mm ± 0.82 mm) on SMV group while CONTROL group showed less gain (0.54 mm ± 0.50 mm; p˂0.05). SMV Group showed 2.9% sites with bone resorption in region of radiographic alveolar crest while CONTROL group showed 18.6% (p˂0.05). In conclusion, SMV promoted additional improvement in the clinical, hematologic and radiographic parameters in patients with CP following SRP, preventing bone resorption and inducing bone formation.